Moving goals. Goal-work in Parkinson's disease rehabilitation - Tonnesen, Merete; Nielsen, Claus Vinther; Andersen, Rikke Sand (Frontiers in Rehabilitation Sciences, 2022)
Chronic diseases often demand considerable work by patients: they must adhere to medical regimes and engage with social and embodied discontinuities. In Denmark, rehabilitees in Parkinson's disease rehabilitation talk about Parkinson's as their new job. In this article, we introduce goal-work as an optical lens to enlarge and explore the micro-social practices that concern a core practice in rehabilitation where professionals and rehabilitees set goals for the future and work towards the goals. To work with goals adds a new task to living with Parkinson's. Rehabilitation research tends to focus on the actual goal-setting meeting. Drawing on data from long-term ethnographic fieldwork on goals and their setting in Parkinson's disease rehabilitation, we show how participants in rehabilitation imagine, set, enact, review or share their rehabilitation goals, and how goals are worked with before and after the goal-setting meeting, across settings. We conceptualize these micro-social practices as goal-work, which we argue is a spatio-temporal process. The concept of goal-work emphasizes the fact that goal-setting is one event in a string of goal-related activities, and it turns our attention to the intersubjective dimensions inherent in goal-work, such as the role of relatives and how acts of imagination and acts of sharing form part of goal-work.